Main principals of cooperation of preschool educational establishments with families of their educatees - Olena Datsun (Vasyl Stefanyk Precarpathian National University, 2018)
The importance of family upbringing has been spotted in the article. The cooperation between a family and preschool educational establishment that is of high value has been illustrated. The main principals of their cooperation have been singled out. The effective forms and methods of their interrelation have been grounded. Key words: preschool educational establishment, family, interrelation, cooperation, partnership, self-trust, self-respect.